KETAHANAN KELUARGA DI MASA PANDEMI COVID 19 DIHUBUNGKAN DENGAN UNDANG-UNDANG DAN MAQASHID SYARIAH - Yandi Maryandi; Shindu Irwansyah; TB Hadi Sutikna (Tahkim (Jurnal Peradaban dan Hukum Islam), 2021)
Family resilience is a family condition that has tenacity and toughness and contains physical and material abilities in order to live independently and develop themselves and their families to live harmoniously in increasing physical and spiritual well-being and happiness. To deal with this cultural attack of globalization coupled with the COVID-19 pandemic crisis which resulted in many impacts on divorce, it is necessary to have good family resilience and the quality of religious education applied in social life. Family resilience is the key to successful development in a country that will have an impact on national resilience and the sustainability of a nation. The formulation of the problem is summarized in the objectives of this study, namely; To know the concept of family resilience according to Indonesian law and Maqashid Syari'ah, as well as to find the right solution and form of family resilience during the COVID-19 pandemic to avoid division and divorce. From this research, the long-term goal is to be able to regenerate the spirit of maintaining family resilience in an increasingly massive era of globalization, with the support of the government and religious education, it is hoped that the quality of family resilience will be better. The research methodology used is a qualitative research method through literature study, with normative juridical research and secondary data sources collected by documentary and interview methods and then analyzed descriptively qualitatively so that the level of synchronization, appropriateness of norms, and so on are known.